2016
DOI: 10.1016/j.cub.2015.12.069
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and Connectivity Govern Actin Network Contractility

Abstract: SUMMARY Actomyosin contractility plays a central role in a wide range of cellular processes, including the establishment of cell polarity, cell migration, tissue integrity, and morphogenesis during development. The contractile response is variable and depends on actomyosin network architecture and biochemical composition. To determine how this coupling regulates actomyosin-driven contraction, we used a micropatterning method that enables the spatial control of actin assembly. We generated a variety of actin te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
303
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(333 citation statements)
references
References 41 publications
25
303
5
Order By: Relevance
“…Precisely how SF network heterogeneities arise and evolve represents an important open question, and it is possible that this may be a function of the cell's adhesive and spreading history. Indeed, our findings complement the recent, elegant demonstration that patterning reconstituted actomyosin network architecture can modulate contractility (34). Development of analogous micropatterning strategies for living cells may make it possible to test the hypotheses raised in our study by engineering the details of the internal SF network through strategic placement of adhesions.…”
Section: Discussionsupporting
confidence: 78%
“…Precisely how SF network heterogeneities arise and evolve represents an important open question, and it is possible that this may be a function of the cell's adhesive and spreading history. Indeed, our findings complement the recent, elegant demonstration that patterning reconstituted actomyosin network architecture can modulate contractility (34). Development of analogous micropatterning strategies for living cells may make it possible to test the hypotheses raised in our study by engineering the details of the internal SF network through strategic placement of adhesions.…”
Section: Discussionsupporting
confidence: 78%
“…Yet the basic principles underlying the relationship between actin ring organization and function have only begun to be unraveled, due to technical limitations of visualizing the actin network organization within rings (e.g., by electron or super-resolution fluorescence microscopy). In a recent study, the role of actin network organization and connectivity for actomyosin ring contraction was analyzed (Ennomani et al, 2016). As expected, it was found that in the absence of actin cross-linkers, ordered anti-parallel (sarcomere-like) bundles showed a higher level of contractility than disordered actin networks or actin bundles with mixed polarity.…”
Section: Discussionmentioning
confidence: 74%
“…If myosin slides actin filaments that are structurally incompatible with contraction, the filaments buckle and break 26 . Therefore, myosin not only contracts, but also remodels the cortex 27,28 . In addition, myosin can induce flows of free actin filaments into aster-like formations 29,30 , and potentially transport proteins via co-assembly with the cargo-binding protein MYO18A 31 .…”
Section: [H1] Structure Of the Cortical Cytoskeletonmentioning
confidence: 99%